Analisis Metode Pendidikan Islam dalam Al-Qur'an: Kajian QS. Hud Ayat 61-68 - Irfan, Rengga; Khuluqi, Syafiyatul (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The aim of this research is to explore the Islamic educational methods contained in Surah Hud, verses 61-68. Current phenomena indicate that there are still many errors in teaching methods, both within and outside of school environments. One notable issue is that teachers often hesitate to administer punishment to students due to concerns about being perceived as engaging in violence. Therefore, this study seeks to revisit appropriate educational methods based on the guidance of the Qur'an. This research is a qualitative library research using content analysis as the analysis method. Focus of this research is on Surah Hud, verses 61-68, which is analyzed based on the interpretations of Tafsir Al-Azhar by Buya Hamka, Tafsir An-Nur by Teungku Hasbi Ash-Shidiqi, and Tafsir Al-Misbah by Quraish Shihab. The findings reveal that there are five Islamic educational methods in Surah Hud, verses 61-68, namely: a) the lecture method, b) the question and answer method, c) the demonstration method, d) the assignment method, and e) the Targhib (reward) and Tarhib (punishment) method. These methods can serve as a model that can be applied in contemporary education. Their relevance remains strong today, although their application may require adjustments and modifications in line with modern developments.